Observationally constrained estimates of the annual Arctic sea-ice volume budget 2010–2022 - Harold Heorton; Michel Tsamados; Jack Landy; Paul R. Holland (Annals of Glaciology)
Sea-ice floating in the Arctic ocean is a constantly moving, growing and melting layer. The seasonal cycle of sea-ice volume has an average amplitude of $10\,000\,km^3$ or 9 trillion tonnes of sea ice. The role of dynamic redistribution of sea ice is observable during winter growth by the incorporation of satellite remote sensing of ice thickness, concentration and drift. Recent advances in the processing of CryoSat-2 radar altimetry data have allowed for the retrieval of summer sea-ice thickness. This allows for a full year of a purely remote sensing-derived ice volume budget analysis.